The role of ERNDIM diagnostic proficiency schemes in improving the quality of diagnostic testing for inherited metabolic diseases. Issue 5 (23rd May 2022) - Mathis, Déborah; Croft, Joanne; Chrastina, Petr; Fowler, Brian; Vianey‐Saban, Christine; Ruijter, George J. G.
Abstract: External quality assurance (EQA) is crucial to monitor and improve the quality of biochemical genetic testing. ERNDIM (www.erndim.org ), established in 1994, aims at reliable and standardized procedures for diagnosis, treatment and monitoring of inherited metabolic disease (IMD) by providing EQA schemes and educational activities. Currently, ERNDIM provides 16 different EQA schemes including quantitative schemes for various metabolite groups, and interpretive schemes such as diagnostic proficiency testing (DPT). DPT schemes focus on the ability of laboratories to correctly identify and interpret abnormalities in authentic urine samples across a wide range of IMDs. In the DPT schemes, six samples each year are distributed together with clinical information. Laboratories choose and perform the tests needed to reach a diagnosis. Data were collected on 345 samples, distributed to up to 105 laboratories worldwide. Diagnostic proficiency (the % of total points possible for all participating laboratories within a scheme for analysis and interpretation) ranged widely: amino acid disorders ( n = 20), range 33%–100%, mean 84%; organic acid disorders ( n = 35), range 14%–100%, mean 84%; lysosomal storage disorders ( n = 13), range 20%–97%, mean 73%; purine/pyrimidine disorders ( n = 9), range 37%–100%, mean 70%; miscellaneous disorders ( n = 8), range 17%–100%, mean 65%; no IMD, range 65%–95%, mean 85%. When a sample with the same disorder was distributed in a subsequent survey, performance improved in 75 cases with no improvement seen in 32, suggesting overall improvement of performance. ERNDIM diagnostic proficiency testing is a valuable activity which can help to assess laboratory performance, identify methodological/technical challenges, be informative during quality audits and contribute to a better clinical appreciation of diagnostic uncertainty.